2017
DOI: 10.1159/000480346
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Is Involved in Cochlear Cell Apoptosis in a Cisplatin-Induced Ototoxicity Rat Model

Abstract: Endoplasmic reticulum (ER) stress arises when excessive improperly folded proteins accumulate in the ER lumen. When ER stress occurs, the unfolded protein response (UPR) is subsequently activated to restore ER proteostasis. However, severe ER stress leads to apoptosis. Recent studies have suggested that cisplatin cytotoxicity may be related to ER stress. The purpose of this study was to determine whether ER stress participates in cochlear cell apoptosis in a cisplatin-induced ototoxicity rat model and to also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…This study revealed that treatment with cisplatin increased the levels of active caspase-12 in cochlear cells, a finding indicative of cisplatin-induced activation of ER-specific apoptosis. The increased expression of CHOP and cleaved caspase-9 suggested a close relationship between severe ER stress and mitochondria-dependent apoptosis in cochlear cells of cisplatin-treated rats [50].…”
Section: Hearing Lossmentioning
confidence: 89%
“…This study revealed that treatment with cisplatin increased the levels of active caspase-12 in cochlear cells, a finding indicative of cisplatin-induced activation of ER-specific apoptosis. The increased expression of CHOP and cleaved caspase-9 suggested a close relationship between severe ER stress and mitochondria-dependent apoptosis in cochlear cells of cisplatin-treated rats [50].…”
Section: Hearing Lossmentioning
confidence: 89%
“…C/EBP genes are also involved in various biological functions. For example, C/EBPζ is involved in cochlear cell apoptosis in rats [41] and may coregulate the inner ear development with GATA binding protein 2 (GATA2) [42]; Hata et al (2005) reported that C/EBPβ promotes the differentiation of mouse mesenchymal cells into the osteoblast lineage in cooperation with Runt-related transcription factor 2 (Runx2) transcription factor [43]. Allele-speci c induction of Interleukin 1 beta (IL-1b) expression by C/EBPβ contributes to increased tuberculosis susceptibility in humans [44].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of research has been done for the hearing protection in basic principles and clinical applications. Some reports from the point of cell biology demonstrated that the unfolded protein response (UPR) triggered by endoplasmic reticulum (ER) stress is deeply involved in the pathogenesis of sensorineural hearing loss, inducing apoptosis in cochlear hair cells, stria vascularis and spiral ganglion cells [9,10,11,41,42,43,44]. It has been widely reported that ER stress induces apoptosis, which depends on the activation of the caspase cascade [14,40].…”
Section: Discussionmentioning
confidence: 99%